Wireless Evolution: 1G To 4 G - An Assessment - Hooi, Peh Tiong (2002)
For the Next 20 years, higher efficiency, high speed wireless data, multimedia content and applications will further fuel mobile telephony sector's growth worldwide with the introduction of Third Generation (3G) and Fourth Generation (4G) mobile services.